Revision of the Neotropical genus Alloraphes Franz (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2013)
The Neotropical genus Alloraphes Franz belonging to the tribe Cyrtoscydmini is revised. Alloraphes is redefined based on a detailed morphological study, and Parastenichnaphes myrmecophilus (Franz) is transferred back to Alloraphes, where it was originally placed. Alloraphes jamaicae Franz, A. peruanus Franz, A. lenkoi Franz, A. yucatani Franz, A. chiapasensis Franz and A. myrmecophilus Franz, stat. rest. are redescribed; A. dentatus sp. n. from Peru and A. peckorum sp. n. from Bolivia are described. Alloraphes magnus Franz and A. bolivarensis Franz are treated as species inquirendae pending further study. The placement of ?Alloraphes magnus, known from a single female only, remains unclear. The type material of A. bolivarensis was not found in the Franz Collection and the original description hardly allows for the species identification.